Association of plasma asymmetrical dimethylarginine (ADMA) with elevated vascular superoxide production and endothelial nitric oxide synthase uncoupling: implications for endothelial function in human atherosclerosis. - Antoniades, C; Shirodaria, C; Leeson, P; Antonopoulos, A; Warrick, N; Van-Assche, T; Cunnington, C; Tousoulis, D; Pillai, R; Ratnatunga, C; Stefanadis, C; Channon, K (2009)
BACKGROUND: Asymmetrical dimethylarginine (ADMA), an endogenous inhibitor of endothelial nitric oxide synthase (eNOS), is considered to be a risk factor for atherosclerosis. However, the mechanisms relating ADMA with vascular function have been evaluated in vitro and in animal models, but its effect in human vasculature is unclear. AIMS: We examined the impact of serum ADMA on endothelial nitric oxide (NO) bioavailability and vascular superoxide radical (O2-) production in patients with advanced atherosclerosis. METHODS AND RESULTS: Paired samples of saphenous veins (SVs) and internal mammary arteries (IMAs) were collected from 201 patients undergoing coronary bypass surgery, and serum ADMA was measured pre-operatively. The vasomotor responses of SV segments to acetylcholine (ACh) and bradykinin (Bk) were evaluated ex vivo. Vascular O2- was measured in paired SV and IMA by lucigenin-enhanced chemiluminescence. The l-NAME-inhibitable as well as the NADPH-stimulated vascular O2- generation was also determined by chemiluminescence. High serum ADMA levels were associated with decreased vasorelaxation of SV to ACh (P < 0.05) and Bk (P < 0.05). Similarly, high serum ADMA was associated with higher total O2- production in both SVs and IMAs (P < 0.05) and greater L-NAME-inhibitable vascular O2- (P < 0.05). However, serum ADMA was not associated with NADPH-stimulated vascular O2-. In multivariable linear regression, serum ADMA was independently associated with vascular O2- in both SVs [beta (SE): 0.987 (0.412), P = 0.019] and IMAs [beta (SE): 1.905 (0.541), P = 0.001]. Asymmetrical dimethylarginine was also independently associated with maximum vasorelaxation in response to both ACh [beta (SE): 14.252 (3.976), P = 0.001] and Bk [beta (SE): 9.564 (3.762), P = 0.013]. CONCLUSION: This is the first study that demonstrates an association between ADMA and important measures of vascular function, such as vascular O2- production and NO bioavailability directly in human vessels. Although serum ADMA has no effect on NADPH-stimulated superoxide in intact vessels, it is associated with greater eNOS uncoupling in the human vascular endothelium of patients with coronary artery disease.